46 Change in Regional Adipose Tissue and Intrahepatocellular Lipid in Healthy Fully Breast-Fed Babies, Between Birth and Three Months. (October 2012) - Gale, C; Jeffries, S; Logan, KM; Parkinson, JR; Uthaya, S; Thomas, EL; Durigel, G; Bell, JD; Modi, N
Abstract : Background and aims: Total adiposity doubles in early infancy 1, however there exists little data describing the change in adipose tissue (AT) distribution and intrahepatocellular lipid (IHCL) over this period. In adults AT distribution and IHCL have important health implications 2 . We aimed to measure the change in AT distribution and IHCL in healthy breastfed babies. Design: Healthy, term, appropriate weight for gestational age infants were recruited from the postnatal ward at Chelsea and Westminster Hospital. Magnetic resonance images and proton spectra were acquired after birth and at 2–3 months as previously described 3, 4 . IHCL results are presented as the ratio CH2 /water. Results: We studied 32 infants. Change in AT and IHCL are presented in table 1 . While total AT volume doubled, there was variation in the magnitude of change in the different regional AT compartments. Conclusions: Growth of different regional AT depots occurs at different rates, and IHCL increases in early infancy. The physiological significance of these novel findings is uncertain. References: 1. Gale C AJCN 2012; 2. Fabbrini PNAS 2009; 3. Modi N Pediatr Res 2006; 4. Thomas EL ADCFN 2008.